The equation of perpendicular bisector of A(-6, -4 ) and B(2, 0) is y = -2x - 6
Solution:
Given that we have to find the equation of perpendicular bisector of A(-6, -4 ) and B(2, 0)
A perpendicular bisector, bisects a line segment at right angles
To obtain the equation we require slope and a point on it
Find the midpoint and slope of the given points and then we can find the equation
Find the midpoint:
Given points are A(-6, -4 ) and B(2, 0)
The midpoint is given as:
![m(x, y)=\left((x_(1)+x_(2))/(2), (y_(1)+y_(2))/(2)\right)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6x5weme4d58yo731nlgop6s7glqmwyanz8.png)
![\text {Here } x_(1)=-6 ; y_(1)=-4 ; x_(2)=2 ; y_(2)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3ynh7y1ew2xql9n1hh8eukbadic67wll1l.png)
Substituting the values we get,
![\begin{aligned}&m(x, y)=\left((-6+2)/(2), (-4+0)/(2)\right)\\\\&m(x, y)=(-2,-2)\end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pxlvdj9fzrqdp7x5imr602vv95fp7qbu7r.png)
Find the slope of given points:
![m=(y_(2)-y_(1))/(x_(2)-x_(1))](https://img.qammunity.org/2021/formulas/mathematics/college/wdytxpxq579urepn831wtazj0i7y16uhnc.png)
![m=(0-(-4))/(2-(-6))\\\\m = (4)/(8)\\\\m = (1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/adpp1icchxwb1689o6htcn1mzmysjjortf.png)
Then the slope of perpendicular bisector is given as:
We know that product of slopes of given line and slope of line perpendicular to it is equal to -1
Let the slope of perpendicular bisector be
![m_1](https://img.qammunity.org/2021/formulas/physics/high-school/f4xgj9jgqryenxhcbcvu2dktbvnuvmmv5s.png)
![(1)/(2) * m_1 = -1\\\\m_1 = -2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fsgtez2v7eqgz1upimnjevqoado98rn3tv.png)
Find the equation of line with slope -2 and point (-2, -2)
The equation of line in slope intercept form is given as:
y = mx + c -------- eqn 1
Where "m" is the slope and "c" is the y - intercept
Substitute (x, y) = (-2, -2) and slope m = -2 in eqn 1
-2 = -2(-2) + c
-2 = 4 + c
c = -2 - 4
c = -6
Substitute c = -6 and m = -2 in eqn 1
y = -2x - 6
Thus the required equation of perpendicular bisector is found